Factors affecting adoption of agroforestry practices by farmers in Cameroon - Nkamleu, G.B.; Manyong, Victor M. (Springer, 2005)
This paper presents empirical evidence on the impact of socio-economic factors on the adoption of agroforestry practices in Cameroon. The analysis uses primary farm-level data collected from June to December 1996. Three major provinces of the country were covered, namely Centre, Southwest and Northwest Several agroforestry technologies have been promoted among farmers in the zone, including alley farming, improved fallow, live fencing, cut-and-carry fodder and apiculture. The status of adoption of each agroforestry practice is described and factors that affect adoption identified. These are gender of farmer, household family size, level of education, farmer’s experience, membership within farmers’ associations, contact with research and extension, security of land tenure, agroecological zone, distance of the village from nearest town, village accessibility and income from livestock. Research findings indicate that since factors affecting farmers’ adoption of agroforestry practices differ across techniques, generalisation is to be avoided.